International Partnership Failures in the Context of Family Small and Medium Enterprises Internationalisation - Kampouri, Katerina; Hajidimitriou, Yannis (European Journal of Family Business, 2023)
This study aims to address the question of why the efforts of family Small and Medium Enterprises (family SMEs) to develop international partnerships fail. In particular, it draws on the network theory of internationalisation and SEW perspective and explores how family managers’ interpretation of the behaviour of potential international partners can lead to the failure of the attempt to develop an international partnership in the context of family SMEs internationalisation. To do so, it conducts a multiple case study of four internationalised Greek family SMEs in the food and beverages sector. The findings suggest that family managers set strict criteria, regarding their expectations about international partners’ behaviour when evaluating the potential international partners, which emerge from family managers’ effort to fulfil family goals (e.g., the preservation of family harmony and family reputation), and reveal that the family managers’ priority on the fulfilment of family goals can hinder the international partnership development process. These findings build upon the limited, yet important, family SMEs literature on international partnership failures and enrich previous networking theories about family SMEs’ internationalisation.